List of Orchid Species along the Northern Trekking Route of Mount Binaiya, Seram Island, Maluku - Indonesia - Wijaya, I Made Saka; Purnomo, Purnomo (Graduate Study of Environmental Sciences, Postgraduate Program of Udayana University, 2024)
Orchidaceae is widely distributed on Earth with major distribution in the tropical regions, including Indonesia. Seram Island located in Maluku Province Indonesia has a high potential to become a habitat for various species of Australasian orchids. Orchid diversity tends to be related to altitude variations in the area that indirectly contribute to creating microclimate variations. One area on Seram Island with various variations in altitude is Mount Binaiya within the Manusela National Park area. This study aims to identify orchid species found on Mount Binaiya. The exploration method was used on the northern trekking route of Mount Binaiya, divided into Waisamata, Kanikeh, Waiansela, and Waihuhu areas. Based on the result, 47 species of orchids were obtained, which belong to the subfamilies Epidendroideae (35 species), Orchidoideae (11 species), and Vanilloideae (1 species). Based on the life form, 25 species were epiphytes, while 22 species were terrestrial orchids. Waisamata had the highest number of species (23 species), followed by Waiansela (14 species), Waihuhu (14 species), and Kanikeh (8 species). Of all these species, some that need further research are Corybas spp., Cyrtosia nana, Pterostylis papuana, Glomera papuana, and Mediocalcar pygmaeum. Some species are new records in their distribution or rediscoveries of existing records.